Colonization Factors of Enterotoxigenic Escherichia coli - Madhavan, T P Vipin; Sakellaris, Harry (Advances in Applied Microbiology, 2015)
Enterotoxigenic Escherichia coli (ETEC) is a major cause of life-threatening diarrheal disease around the world. The major aspects of ETEC virulence are colonization of the small intestine and the secretion of enterotoxins which elicit diarrhea. Intestinal colonization is mediated, in part, by adhesins displayed on the bacterial cell surface. As colonization of the intestine is the critical first step in the establishment of an infection, it represents a potential point of intervention for the prevention of infections. Therefore, colonization factors (CFs) have been important subjects of research in the field of ETEC virulence. Research in this field has revealed that ETEC possesses a large array of serologically distinct CFs that differ in composition, structure, and function. Most ETEC CFs are pili (fimbriae) or related fibrous structures, while other adhesins are simple outer membrane proteins lacking any macromolecular structure. This chapter reviews the genetics, structure, function, and regulation of ETEC CFs and how such studies have contributed to our understanding of ETEC virulence and opened up potential opportunities for the development of preventive and therapeutic interventions.